Edoxaban: front-line treatment for brachiocephalic vein thrombosis in primitive mediastinal seminoma: A case report and literature review. Issue 34 (26th August 2022) - Fioretti, Agnese Maria; Leopizzi, Tiziana; Puzzovivo, Agata; Giotta, Francesco; Lorusso, Vito; Luzzi, Giovanni; Oliva, Stefano
Abstract : Rationale: Venous thromboembolism is a feared frequent complication of cancer with a 2-way relationship. Low molecular weight heparin is the mainstay of treatment. The use of direct oral anticoagulants is supported by established evidence for the treatment of deep vein thrombosis also in active cancer and they are prioritized over low molecular weight heparin for cancer-associated thrombosis according to current guidelines. However, upper limb deep vein thrombosis is poorly studied with scant data on the use of direct oral anticoagulants in noncatheter-related deep vein thrombosis. We report the case of a patient with noncatheter-related deep vein thrombosis and a rare tumor site effectively and safely treated with a direct oral anticoagulant, edoxaban, after lack of efficacy with low molecular weight heparin. Patient concerns: A 35-year-old man with primitive mediastinal seminoma presented at our Cardio-Oncology Unit for prechemotherapy assessment. Diagnosis: Persistent brachiocephalic deep vein thrombosis, despite full-dose enoxaparin, was detected at ultrasonography. Intervention: We decided to switch the anticoagulant treatment from enoxaparin to edoxaban. Outcome: The 3-month ultrasonography showed almost total regression of the deep vein thrombosis without any adverse effects and a good patient compliance. Lessons: We conducted a literature review on upper limb deep vein thrombosis, since its management is challenging due to inconsistency of evidence. This report highlights the benefits of direct oral anticoagulants compared to low molecular weight heparins in cancer-associated thrombosis therapy in terms of efficacy, safety and ease of use.